2000
DOI: 10.1128/aem.66.5.1953-1959.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Chemical Composition of Enterococcus faecalis in the Viable but Nonculturable State

Abstract: The viable but nonculturable (VBNC) state is a survival mechanism adopted by many bacteria (including those of medical interest) when exposed to adverse environmental conditions. In this state bacteria lose the ability to grow in bacteriological media but maintain viability and pathogenicity and sometimes are able to revert to regular division upon restoration of normal growth conditions. The aim of this work was to analyze the biochemical composition of the cell wall of Enterococcus faecalis in the VBNC state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
145
1
10

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 43 publications
11
145
1
10
Order By: Relevance
“…damselae (Fouz et al 1998). However, the increase in biovolume found for VBNC cells of Listonella pelagia cultured in a 16 ‰ medium, and the spheroid morphology, would suggest that although membrane activity is maintained, the cells are under osmotic stress implying an alteration of the cell wall, as reported by Signoretto et al (2000). Yet in our case it should be pointed out that changes in cell shape and size could not be related to changes in the membrane protein profiles.…”
Section: Discussioncontrasting
confidence: 49%
“…damselae (Fouz et al 1998). However, the increase in biovolume found for VBNC cells of Listonella pelagia cultured in a 16 ‰ medium, and the spheroid morphology, would suggest that although membrane activity is maintained, the cells are under osmotic stress implying an alteration of the cell wall, as reported by Signoretto et al (2000). Yet in our case it should be pointed out that changes in cell shape and size could not be related to changes in the membrane protein profiles.…”
Section: Discussioncontrasting
confidence: 49%
“…In general, a spiral to coccoid conversion was more rapid in broth than on solid media, most likely due to the dissolved toxic substances enhancing the coccoid transformation (Moran & Upton, 1987b ;Coudron & Statton, 1995). The ability to delay the spiral to coccoid conversion may be beneficial in the production of cell surface antigens for immunodiagnostic tests since such conversion has been shown to induce changes in the cell wall composition of H. pylori and other bacteria (Costa et al, 1999 ;Signoretto et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1d, 2d, and 3d). In an earlier study, it was shown that there were modifications in the peptidoglycan of the bacterial cell wall of these dormant cells (Signoretto et al 2003). Subsequently, it was suggested that peptidoglycon hydrolysis driven by the antidormancy factor (also called as resuscitation promoting factor) is a key in vivo step in the revitalization of dormant cells, resulting in cell division (Mukamolova et al 1998; review by Keep et al 2006 and references therein).…”
Section: Bioprocess Implicationsmentioning
confidence: 99%